Implications of Microarray Technology in Forensic Medicine - Shruti R. Kuril; Anshu Priya (Indian Journal of Forensic Medicine and Pathology, 2025)
Background: In Forensic medicine, microarray technology has an immense impact in the areas of investigation, to conduct in-depth Single Nucleotide Polymorphism (SNP) analysis in forensic phenotyping. That allows for the probabilistic prediction of externally visible characteristics (EVCs), such eye and hair colour, and yields useful leads for identifying suspects. The use of microarray technology to estimate the Postmortem Interval (PMI), or time since death, is another area of active research. Moreover, by observing post-mortem, gene expression, microbial DNA, and identi𿿿cation through biologicalÁuids like saliva, CSF, venous blood, menstrual blood, and semen, researchers hope to increase PMI accuracy. These developments and implications of microarrays in forensic science allows for more enhanced and informative genetic analyses, ultimately strengthening forensic investigations. Objective: This review aims to evaluate the current applications and future directions of microarray-based techniques in forensic medicine. Methods: A systematic search was conducted in PubMed, Scopus, Web of Science, Research Gate and Google Scholar for studies published between January 2000 to March 2025. Studies focusing on forensic applications of microarrays, including gene expression pro𿿿ling, identi𿿿cation of bodyÁuids, time of death etimation, and toxicological assessments were included. Results: Out of 789 initially identi𿿿ed articles, 34 studies met the inclusion citeria. Microarrays demonstrated signi𿿿cant utility in identifying speci𿿿c gene expression tterns related to postmortem interval estimation, tissue-speci𿿿c markers, and xin exposure. However, variability in sample preservation, data interpretation, and lack of standardization limit its widespread forensic adoption. Conclusion: Microarray technology shows promising potential in forensic medicine. Integrating it with traditional methods and next-generation sequencing could enhance accuracy and reliability in forensic investigations.